Quantitative systems modeling approaches towards model-informed drug development: Perspective through case studies - Verma, Meghna; Gall, Louis; Biasetti, Jacopo; Di Veroli, Giovanni Y.; Pichardo-Almarza, Cesar; Gibbs, Megan A.; Kimko, Holly (Frontiers in Systems Biology, 2023)
Quantitative systems pharmacology modeling has become an increasingly popular approach impacting our understanding of disease mechanisms and helping predict patients’ treatment responses to facilitate study design or development go/no-go decisions. In this paper, we present examples of QSP modeling applications to highlight the notable contributions and opportunities that these approaches are to offer during the drug development process. We also consider the barriers to successful applications; outline the factors required to support the success of these modeling approaches; and provide insights for a strategy to enhance acceptance by the regulatory agencies.